Connecting the dots: Rethinking farming systems to deliver multiple services - Castro Nunez, Augusto (2025)
During a recent planning meeting for the Alliance’s Latin America and the Caribbean (LAC) team, I shared a reflection from a field visit to Zambia’s Copperbelt region, which sits on the border region between northern Zambia and the southeastern Democratic Republic of Congo.